Between diagnostic intent and uniform tasks: Teachers’ planning for differentiated learning in arts education - Dwi Wulandari; Eni Puji Astuti; Trie Hartiti Retnowati (Journal of Research in Instructional, 2026)
This study examines how arts teachers in Indonesia plan differentiated learning under Kurikulum Merdeka and how such planning may be interpreted through the lens of creative pedagogy. This study employed a multi-source qualitative design using triangulative thematic analysis of two textual corpora: 35 open-ended online survey responses and 21 verified lesson plans/teaching modules from arts teachers in the Special Region of Yogyakarta and Nusa Tenggara Barat, Indonesia. The findings show that teachers generally understand differentiation as a pedagogical ideal centred on learners’ needs, interests, abilities, and learning profiles. In planning practice, however, differentiation was materialised mainly through variation in resources, media, and general classroom activities, such as projects, discussions, presentations, and reflections. While diagnostic assessment, enrichment, and remedial support were frequently mentioned, the linkage between assessment data and genuinely differentiated instructional design remained weak. Many lesson plans retained shared workflows, common core tasks, and relatively standardised outputs across diverse learners. The study concludes that arts teachers have moved towards procedural responsiveness, yet differentiation often remains thin rather than pedagogically plural. These findings emphasise the urgency of a stronger shift from surface variation towards meaningful pedagogical plurality in arts lesson planning.